Recent Advances in Suppressing Sn²⁺ Oxidation in Sn–Pb-based Perovskite Solar Cells - Xia, Xuchen (Transactions on Environment, Energy and Earth Sciences, 2026)
Tin-lead (Sn-Pb) perovskite, a new solar energy material with superior energy-related characteristics, is the material of choice for the next generation of high-efficiency solar panels. Its single big flaw, however, is that the tin is unstable and readily "rusts" or oxidizes, a process that causes defects, which harms the electrical characteristics, constitutes waste of energy, reduces the power output of the solar cell and speeds up its degradation. The answer to this problem is essential. The purpose of this review paper is to survey the various latest ways of inhibiting this tin oxidation. To this end, first the paper discusses the chemical reasons for the instability of the tin. It then goes through the latest approaches in which there are three major approaches: changing the initial formulation of the chemicals so as to offer protection to the tin from the start, addition of some special protecting substances which will act as antioxidants to prevent against or overcome the defects, and lastly the strengthening of the union between the layers making up the solar cell. In analyzing these, it is expected that the problems lying ahead will be brought into sharp focus and this will indicate the field of future research on tin-lead perovskite solar cells, leading to the production of stable high efficiency (Sn-Pb) perovskite solar cells.